Integrated multi-omics analysis reveals the role of nitrogen application in seed storage protein metabolism and improvement of inferior grains in smooth bromegrass - Ou, Chengming; Zhao, Shiqiang; Jia, Zhicheng; Sun, Shoujiang; Wang, Juan; Mi, Chunjiao; Shi, Jinyu; Li, Changran; Mao, Peisheng (Frontiers in Plant Science, 2025)
This study explored the effects of nitrogen application on superior and inferior grains in smooth bromegrass (Bromus inermis) to provide insights for improving seed quality and yield. The study was conducted using a randomized block design with two nitrogen treatments (0 and 200 kg·N·ha-¹) during the 2021–2022 growing seasons. Seed dry weight, fresh weight, and storage protein content were measured at multiple stages after anthesis. PacBio full-length transcriptome sequencing generated a comprehensive transcriptome consisting of 124,425 high-quality transcripts, and metabolomic profiling were performed across developmsental stages. Genetic transformation in Arabidopsis was used to validate gene function. Nitrogen application significantly increased seed dry and fresh weights and storage protein content, particularly gliadin and glutelin. Metabolomic and transcriptomic analyses revealed that nitrogen treatment upregulated glutamate and asparagine levels and enhanced nitrogen transport and protein synthesis pathways. Two α-gliadin nitrogen-responsive genes, BiGli1 and BiGli2, were identified. Overexpression of these genes in Arabidopsis confirmed their role in regulating seed size and vigor. This study highlights the critical role of α-gliadin in enhancing seed quality, particularly in promoting the development of inferior grains, offering valuable insights for the development of high-yield seed varieties and the optimization of specialized forage seed production.